How we'll live on Mars - Petranek, Stephen L., ....- (New York : TED Books, Simon & Schuster, 2015)
It sounds like science fiction, but Stephen Petranek considers it fact: Within twenty years, humans will live on Mars. We'll need to. In this book that mixes business, science, and human reporting, Petranek makes the case that living on Mars is an essential back-up plan for humanity and explains in detail just how it will happen. The race is on. Private companies, driven by entrepreneurs, such as Elon Musk, Jeff Bezos, Paul Allen, and Sir Richard Branson; Dutch reality show and space mission Mars One; NASA; and the Chinese government are among the many groups competing to plant the first stake on Mars and open the door for human habitation. Why go to Mars? Life on Mars has potential life-saving possibilities for everyone on earth. Depleting water supplies, overwhelming climate change, and a host of other disasters -- from terrorist attacks to meteor strikes -- all loom large. We must become a space-faring species to survive. We have the technology not only to get humans to Mars, but to convert Mars into another habitable planet. It will likely take 300 years to "terraform" Mars, as the jargon goes, but we can turn it into a veritable second Garden of Eden. And we can live there, in specially designed habitations, within the next twenty years. In this chronicle, Petranek introduces the circus of characters all engaged in an effort to be the first to settle the Red Planet. How We'll Live on Mars brings firsthand reporting, interviews with key participants, and extensive research to bear on the question of how we can expect to see life on Mars within the next twenty years.
The dream -- Das Marsprojekt -- The great private space race -- Rockets are tricky -- Big questions -- The economics of Mars -- Living on Mars -- Making Mars in Earth's image -- The next gold rush -- The final frontier.
"Within twenty years, humans will live on Mars. We'll need to."--Cover.
Keywords: Mars (Planet).; Aeronautics & Astronautics; Astronomy - General; Cloth or Hardcover; Planets -- Environmental engineering; Science; Space Science; Space colonies